2015
DOI: 10.1007/s00345-015-1610-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric validation of a German language version of a PROM for urethral stricture surgery and preliminary testing of supplementary ED and UI constructs

Abstract: The German language USS-PROM shows similar psychometric properties to the English language version. This instrument can be improved by assessing EF by the use of IIEF-5. Further studies with larger patient cohorts are needed to evaluate the significance of measuring UI in urethroplasty patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 34 publications
6
31
2
Order By: Relevance
“…The mean age of the sample in present study was considerably younger than the original study; however, the reliability and internal consistency of the two studies was comparable . In comparison to the German version of MLUTS, the reliability and internal consistency of Persian version was higher that may be because they were candidate of surgery and more severe suffering in German study …”
Section: Discussioncontrasting
confidence: 52%
“…The mean age of the sample in present study was considerably younger than the original study; however, the reliability and internal consistency of the two studies was comparable . In comparison to the German version of MLUTS, the reliability and internal consistency of Persian version was higher that may be because they were candidate of surgery and more severe suffering in German study …”
Section: Discussioncontrasting
confidence: 52%
“…While these cited reports mostly rely on functional outcomes after excision and primary anastomosis, Ahyai et al reported a postoperative de-novo UI and overall UI in 11% and 42% of patients, respectively [5]. In our current study, mean postoperative ICIQ sum score was 9.8, which is higher compared to a mean of 3.4 in a predominantly non-radiogenic stricture reference cohort [16]. Furthermore, more than 50% of patients reported daily leaking and thus, our data corroborate the higher risk of UI following BMGU for radiation-induced strictures.…”
Section: Discussioncontrasting
confidence: 49%
“…Intriguingly, the EQ-5D index value reported in the current series is comparable to those of reference populations after urethroplasty for non-radiogenic strictures [17], indicating no more, no less problems regarding the different generic health profiles. However, the mean EQ VAS score was 65, which is a patient-reported reflection of the perceived overall health state, and this was significantly lower when compared to reference mean scores of 81 [16] and 79 [17] in patients with predominantly non-radiogenic strictures. Consequently and not surprisingly, the long-winded treatment course following PCa diagnosis with the occurrence of urethral stricture as a late UAE appears to have a vital impact on the subjective health state, even though activities of daily living do not seem to be impaired.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In 2013 the same group presented the first paper that prospectively evaluated the USS-PROM reporting continuous relief of patient’s symptoms and QoL in the 2-year follow-up period, setting a reference point which other groups can compare their performances with (10). The USS-PROM was also recently validated to Italian and German (17, 18). …”
Section: Discussionmentioning
confidence: 99%